2013
DOI: 10.1002/2013eo030006
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Improved Maps of Global Cropland

Abstract: Food security is a key global concern. By 2050, the global population will exceed 9 billion, and a 50% increase in annual agricultural output will be required to keep up with demand. There are significant additional pressures on existing agricultural land through increased competition from the biofuel sector and the need to elevate feed production, which is being driven by higher levels of meat consumption in low‐ and middle‐income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 4 publications
0
52
0
1
Order By: Relevance
“…The first step in defining EO requirements for global agricultural monitoring is identifying the areas that require monitoring, namely the locations of global croplands [71]. To this end, Fritz et al (2015) [1] have developed a "best-available" cropland mask that indicates the probability that any 0.0083° (~1 km at the Equator) cell contains cropland based on a suite of existing land cover and cropland masks.…”
Section: Input Datasets: Where To Image?mentioning
confidence: 99%
“…The first step in defining EO requirements for global agricultural monitoring is identifying the areas that require monitoring, namely the locations of global croplands [71]. To this end, Fritz et al (2015) [1] have developed a "best-available" cropland mask that indicates the probability that any 0.0083° (~1 km at the Equator) cell contains cropland based on a suite of existing land cover and cropland masks.…”
Section: Input Datasets: Where To Image?mentioning
confidence: 99%
“…In contrast, the κ-values of GLC2000, GlobCover2005 and MODIS2010 revealed low agreement, which is most likely due to the disagreement in these global land cover products as outlined in e.g. FRITZ et al (2011) andFRITZ et al (2013b). Our preliminary results give us confidence that crowdsourcing is an appropriate tool for gathering up-to-date land cover information of areas that are, for example, not easily accessible or restricted.…”
Section: Discussionmentioning
confidence: 56%
“…Based on our analysis, we are confident that more than 50% of the points were classified correctly. When comparing our dataset with a recently developed hybrid cropland map (FRITZ et al 2013b), we revealed moderate agreement. In contrast, the κ-values of GLC2000, GlobCover2005 and MODIS2010 revealed low agreement, which is most likely due to the disagreement in these global land cover products as outlined in e.g.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations